PERBANDINGAN ALTERNATIF ASPEK PEMAJAKAN BAGI PENYEDIA LAYANAN OVER THE TOP ASING - Ardhiansyah, Hendrie; Nurhidayati, Nurhidayati (Jurnal Pajak dan Keuangan Negara (PKN), 2019)
Over the years, the rise of digital economy has confused countries in their efforts to tax foreign companies without physically presence within their jurisdiction. One of the potential tax revenues that have not been optimally digging comes from the digital sector. The digital economy sector has enormous potential along with the rapid development of information and communication technology, especially the internet. This digital economy market is dominated by internet-based services commonly called Over The Top (OTT) services and is filled with global content owned by foreign companies. This article argues the provisions of taxation for foreign OTT lending providers in England, Australia, India, and Japan. This research used a qualitative non-case study approach. This study outlines the strengths and weaknesses of each alternative.